An eyewitness remembers the century of the Holy Spirit - Synan, Vinson (Grand Rapids, Mich. : Chosen, 2010)
"A historian of Pentecostalism and a highly regarded denominational leader, Synan has written a summary of the seminal moments in the North American Pentecostal movement. Less a memoir and more of a guide to newcomers, the book presents the rise of practices such as speaking in tongues and healings in the first decade of the 20th century and their spread to Protestant and Roman Catholic churches in the 1960s. The book breathlessly portrays events with tired adjectives such as amazing and awesome and incredible. But its simplicity of presentation is a useful shorthand for conveying big events such as the racial breakthroughs of the 1990s and the phenomenal spread of exuberant worship styles to churches outside the movement. A retired dean of Pat Robertson's Regent University divinity school, Synan argues in favor of the prosperity gospel, though he acknowledges excesses on the part of some of its vocal proponents. He is more critical in his views of the new apostolic movement, in which pastors of large churches declare themselves apostles, holding the potential for abuse"--Reed Business Information / Amazon.com.
Foreword / by Jack Hayford -- Introduction -- A child of Azusa Street -- The latter rain and healing revivals -- Protestant neo-Pentecostals -- Catholic Charismatics -- Charismatic concerns and controversies -- New Orleans -- The prosperity gospel -- The third wave -- Racial reconciliation -- Toronto, Brownsville, and Lakeland revivals -- The New Apostolic Reformation Movement -- Things I never expected to see in my lifetime.
Includes bibliographical references (pages 212-217) and index.
Keywords: Pentecostalism -- History